Hubungan Faktor-Faktor Dengan Kejadian ISPA pada Balita Di Puskesmas X Kota Bandung - Suprihatin, Eva (KEPERAWATAN, 2013)
Abstract - West Java Provincial Health Office stated  ISPA is still the first order of  most diseases in children under five in West Java which  equal to 33.44%.  Number of  patients with respiratory infections, diarrhea and pharyngitis increased in the district and the city of Bandung. The incidence of ISPA in Bandung showed an increase, reaching 17 793 in 2012. Factors that cause the incidence of ISPA was low birth weigh, nutritional status, immunization, residential density and physical environment (Maryunani, 2010). The purpose of this study was to identify the relationship between these factors, low birth weigh , nutritional status, immunization, residential density and physical environments ventilation on the incidence of ISPA in children under five in Public Health Community X Bandung. Design research is correlational, using cross sectional and accidental sampling using sampling techniques. Analysis used in this study is the analysis of Chi Square. The population in this study is 327 toddlers, and samples were used that toddlers who come to the clinic for treatment, taken as many as 15% of 327 infants and obtained 50 respondents. Sampling technique. Analysis used in this study by using chi square analysis. The population is 327 toddlers, and the samples used are toddlers who come to the clinic for treatment, taken as many as 15% of 327 infants and obtained 50 respondents. Statistical analysis of data shows that there are associated between low birth weight with acute respiratory infection (p = 0.000 <0.05), was not associated between nutritional status in infants with the incidence of acute respiratory infection (p = 0.134> 0.05), there is a associated between immunization with acute respiratory infection (p = 0.005 <0.05), there was not associated between the density residential with acute respiratory infection (p = 0.552> 0.05), there was not associated between the physical environment (ventilation) with acute respiratory infection (p = 0,790> 0,05). The conclusion that there is a associated between low birth weight and immunization on the incidence of respiratory infections, and there was not associated between nutritional status, residential density and physical environment (ventilation). And suggestions to the clinic to better promote the importance of immunization and prevention of low birth weight babies born in order to reduce the risk of respiratory infection. Keywords: Acute Respiratory Infection In Toddlers, Low Birth Weight, Nutritional Status, Immunization, Residential Density, Physical Environment (Ventilation)  Abstrak - Dinas Kesehatan Propinsi Jawa Barat menyatakan ISPA masih merupakan urutan pertama penyakit terbanyak pada balita di Propinsi Jawa Barat yakni sebesar 33,44%. Jumlah penderita ISPA, diare dan faringitis meningkat di Kabupaten maupun Kota Bandung. Angka kejadian ISPA di Kota Bandung menunjukan peningkatan yaitu mencapai 17.793 pada tahun 2012. Faktor yang menyebabkan kejadian ISPA adalah  BBLR, status gizi, imunisasi, kepadatan tempat tinggal dan lingkungan fisik ( Maryunani, 2010 ). Tujuan penelitian ini untuk mengidentifikasi hubungan antara faktor-faktor ISPA yaitu BBLR, status gizi, imunisasi, kepadatan tempat tinggal dan lingkungan fisik ventilasi terhadap kejadian ISPA pada balita di Puskesmas X Kota Bandung.Desain penelitian yang digunakan adalah korelasional, dengan menggunakan cross sectional dan menggunakan teknik sampling  accidental sampling. Analisa yang digunakan dalam penelitian ini adalah analisa Chi Square. Populasi dalam penelitian ini yaitu 327 balita, dan sampel yang digunakan yaitu balita yang datang berobat ke puskesmas, diambil sebanyak 15% dari 327 balita dan didapat 50 responden. Analisis statistik terhadap data yang diperoleh menunjukan bahwa terdapat hubungan antara BBLR dengan kejadian ISPA pada balita (p=0,000 < 0,05), tidak ada hubungan antara status gizi dengan kejadian ISPA pada balita (p=0,134 > 0,05), ada hubungan antara imunisasi dengan kejadian ISPA pada balita (p=0,005 < 0,05), tidak ada hubungan antara kepadatan tempat tinggal dengan kejadian ISPA pada balita (p=0,552 > 0,05), tidak ada hubungan antara lingkungan fisik ventilasi dengan kejadian ISPA pada balita (p=0,790 > 0,05). Kesimpulan dari penelitian ini bahwa terdapat hubungan antara BBLR dan imunisasi terhadap kejadian ISPA, serta tidak terdapat hubungan antara status gizi, kepadatan tempat tinggal dan lingkungan fisik ventilasi terhadap kejadian ISPA. Dan saran kepada puskesmas supaya lebih mensosialisasikan pentingnya imunisasi dan pencegahan terjadinya kelahiran bayi yang BBLR agar mengurangi resiko terjadinya ISPA. Kata Kunci: ISPA pada balita, BBLR, Status Gizi, Imunisasi, Kepadatan Tempat rancangan survey Tinggal, Lingkungan Fisik (Ventilasi)